INSTRUCTIONAL DESIGN AND TEACHER AGENCY IN TECHNOLOGY-ENHANCED HYBRID LEARNING - Noor Aziz; Pieter Hendriks; Eva Janssen (Yayasan Adra Karima Hubbi, 2026)
Technology-enhanced hybrid learning has transformed contemporary education by integrating digital platforms with face-to-face instruction, yet it raises persistent challenges regarding instructional design coherence and teacher agency in pedagogical decision-making. This study aims to examine the relationship between instructional design and teacher agency in hybrid learning environments and to explore how their interaction influences teaching effectiveness. A qualitative research design based on systematic literature review and interpretive analysis was employed, drawing on peer-reviewed studies, institutional reports, and educational technology frameworks published between 2015 and 2026. Findings reveal that instructional design provides structural guidance for hybrid learning implementation, while teacher agency enables adaptive, context-responsive pedagogical practices. The results further indicate that effective hybrid learning emerges from a dynamic balance between standardized instructional frameworks and teacher autonomy in utilizing digital technologies. Institutional support, technological infrastructure, and professional development significantly influence this balance. The study concludes that instructional design and teacher agency are interdependent constructs that jointly determine the success of technology-enhanced hybrid learning systems, highlighting the need for flexible pedagogical frameworks that empower teachers as active designers of learning.